Pengaruh Inklusi Keuangan terhadap Stabilitas Perbankan Syariah di Indonesia Menggunakan Metode Generalized Least Square - Alwi Muarif Sembiring; Nurlaila, Nurlaila; Nur Ahmadi Bi Rahmani (AKUA: Jurnal Akuntansi dan Keuangan, 2025)
The role of the banking sector in supporting a country's economy is crucial, particularly in facilitating the implementation of national development aimed at fostering economic growth and stability to improve the standard of living of the society. Therefore, this study aims to examine whether financial inclusion has an impact on the stability of Islamic banking in Indonesia, using the Generalized Least Squares (GLS) method. To obtain a clear and measurable understanding, this research employs a descriptive quantitative approach, supported by the GLS method, which addresses issues found in classical assumption testing. The analysis is conducted using Eviews 12 with panel time series data. To measure the financial stability of Islamic banking, financial inclusion is represented by MSMEs and Deposits, while stability is measured using the NPF (Non-Performing Financing) variable. The research findings are as follows: First, the independent variable MSMEs significantly affects NPF. Second, the independent variable Deposits also significantly affects NPF. Third, the F-test indicates that MSMEs and Deposits jointly influence NPF. Thus, financial inclusion has a significant impact on the stability of Islamic banking in Indonesia.